2021
DOI: 10.3390/jcm10194574
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification of Patients with Acute Coronary Syndrome

Abstract: Defining the risk factors affecting the prognosis of patients with acute coronary syndrome (ACS) has been a challenge. Many individual biomarkers and risk scores that predict outcomes during different periods following ACS have been proposed. This review evaluates known outcome predictors supported by clinical data in light of the development of new treatment strategies for ACS patients during the last three decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 86 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…[5][6][7][8] Since early coronary intervention in high-risk patients has consistently been shown to enhance clinical outcomes, risk stratification is crucial. 10,12 In our study, the mean age was 57.21±12.22 years. Santos ES, et al reported age as 59.9±10.6 years.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…[5][6][7][8] Since early coronary intervention in high-risk patients has consistently been shown to enhance clinical outcomes, risk stratification is crucial. 10,12 In our study, the mean age was 57.21±12.22 years. Santos ES, et al reported age as 59.9±10.6 years.…”
Section: Discussionmentioning
confidence: 61%
“…9 As association between TIMI risk score and GRACE score with Syntax score is still debatable due to variability of the findings. 10 Therefore, it is important to generate local data so that both these risk stratification scales can be used extensively to risk stratify patients as soon as they are admitted so that their management can be tailored accordingly. As "National Institute of Cardiovascular Disease (NICVD)" is the major cardiac center of the country and the patient flow is from different socioeconomic status from all over Pakistan and there is marked cultural diversity as well, hence the findings of our study were thought to be more representative of the target population in order to generalize our conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…In the last 40 years, major progress has been made in the management and treatment of ACS, and the prognoses of patients have significantly improved. However, continuous efforts are still being made to predict the outcome of patients with ACS [30]. LV dysfunction is a key prognostic factor in patients presenting ACS.…”
Section: Acute Coronary Syndromesmentioning
confidence: 99%
“…However, the latest European Society of Cardiology (ESC) guidelines downgrade their prognostic importance. 4,5 TIMI risk score was clinically useful in the triage and management of fibrinolysis-eligible patients with STEMI decades ago and included a spectrum of admission variables, such as comorbidities, older age, hypotension, tachycardia, Killip classes II-IV, body weight below 70 kg, anterior STEMI, and more than a 4-hour treatment delay. 6 However, later studies demonstrated, in addition to timely use of primary PCI, other important predictors of prognosis such as prior resuscitation, TIMI III flow after primary PCI, in-hospital cardiogenic shock, bleeding, and acute kidney injury.…”
Section: Introductionmentioning
confidence: 99%